Variability due to climate and chemistry in observations of oxygenated Earth-analogue exoplanets. Issue 1 (17th September 2022) - Cooke, G J; Marsh, D R; Walsh, C; Rugheimer, S; Villanueva, G L
ABSTRACT: The Great Oxidation Event was a period during which Earth's atmospheric oxygen (O2 ) concentrations increased from ∼10 −5 times its present atmospheric level (PAL) to near modern levels, marking the start of the Proterozoic geological eon 2.4 billion years ago. Using WACCM6, an Earth System Model, we simulate the atmosphere of Earth-analogue exoplanets with O2 mixing ratios between 0.1 and 150 per cent PAL. Using these simulations, we calculate the reflection spectra over multiple orbits using the Planetary Spectrum Generator. We highlight how observer angle, albedo, chemistry, and clouds affect the simulated observations. We show that inter-annual climate variations, as well short-term variations due to clouds, can be observed in our simulated atmospheres with a telescope concept such as LUVOIR or HabEx. Annual variability and seasonal variability can change the planet's reflected flux (including the reflected flux of key spectral features such as O2 and H2 O) by up to factors of 5 and 20, respectively, for the same orbital phase. This variability is best observed with a high-throughput coronagraph. For example, HabEx (4 m) with a starshade performs up to a factor of two times better than a LUVOIR B (6 m) style telescope. The variability and signal-to-noise ratio of some spectral features depends non-linearly on atmospheric O2 concentration. This is caused by temperature and chemical column depth variations, as well as generally increased liquid and ice cloud content for atmospheres with O2 concentrations of <1 per cent PAL.